2020
DOI: 10.1128/jvi.02049-19
|View full text |Cite
|
Sign up to set email alerts
|

Novel Insights into the Roles of Bcl-2 Homolog Nr-13 (vNr-13) Encoded by Herpesvirus of Turkeys in the Virus Replication Cycle, Mitochondrial Networks, and Apoptosis Inhibition

Abstract: The Bcl-2 (B cell lymphoma 2)-related protein Nr-13 plays a major role in the regulation of cell death in developing avian B cells. With over 65% sequence similarity to the chicken Nr-13, herpesvirus of turkeys (HVT) vNr-13, encoded by the HVT079 and HVT096 genes, is the first known alphaherpesvirus-encoded Bcl-2 homolog. HVT-infected cells were reported to be relatively more resistant to serum starvation, suggested that vNr-13 could be involved in protecting the cells. Here, we describe CRISPR/Cas9-based edit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 82 publications
0
8
0
Order By: Relevance
“…Some members of the Bcl-2 family are prosurvival, such as BclXL, whose overexpression inhibits apoptosis induced by viral infection ( 12 , 13 ). For example, some viruses encode proteins, such as herpesvirus-encoded Nr-13, that are functional homologs of cellular Bcl-2 proteins and inhibit apoptosis and persist in host cells for the benefit of viral replication ( 14 , 15 ). Bcl-2 inhibits SARS-CoV infection-induced caspase-dependent apoptosis without affecting viral replication kinetics ( 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…Some members of the Bcl-2 family are prosurvival, such as BclXL, whose overexpression inhibits apoptosis induced by viral infection ( 12 , 13 ). For example, some viruses encode proteins, such as herpesvirus-encoded Nr-13, that are functional homologs of cellular Bcl-2 proteins and inhibit apoptosis and persist in host cells for the benefit of viral replication ( 14 , 15 ). Bcl-2 inhibits SARS-CoV infection-induced caspase-dependent apoptosis without affecting viral replication kinetics ( 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…The role of a majority of MDV-encoded proteins and host-virus interactions contributing to the MDV-induced oncogenesis are still to be explored. Following the successful application of the CRISPR/Cas9 system on HVT and MDV genome editing for gene function and virus-host interaction studies [39][40][41][42]50,51] and recombinant vaccine development [37,38,52] with a highly efficient NHEJ repair pathway, we report here the first use of the HDR repair pathway to tag the MDV viral gene pp38 of the vaccine strain CVI988 with V5 and GFP as an alternative of the antibody generation approach. The rapid and efficient tagging of the MDV viral gene provides huge opportunities for gene function studies without the need for generating specific antibodies against the viral proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, a transfection/infection methodology that involves transfection of Cas9/ gRNA expression plasmids into CEF followed by infection of the parental virus, plaque purification, and characterization of the mutant viruses was used for gene deletion of replicating MDV/HVT in CEF cells with NHEJ repair [41,42,51]. Considering the likely high background of the wild-type virus with low efficient HDR-based editing of this approach, we developed a new pipeline for generating mutant MDV with precise mutation using co-electroporation of genomic DNA extracted from MDV-infected CEF, together with a Cas9/gRNA expression plasmid and the donor DNA, followed by an analysis of the formed plaques.…”
Section: Discussionmentioning
confidence: 99%
“…These mammalian and zebrafish counterparts were shown to have a conserved Bcl-2 fold [7]. A recent study showed that vNR13/HVT079 localized to mitochondria and the endoplasmic reticulum [148]. In a functional study, vNR13/HVT079 expression inhibited apoptosis, a vNR13/HVT079 deletion mutant affected the viral replication in vitro, and the expression of vNR13/HVT079 disrupted mitochondrial morphology in HVT-infected cells [148].…”
Section: Herpesviridaementioning
confidence: 99%